ANALYSIS OF STUNTING RISK FACTORS IN CHILDREN IN THE MAGETAN DISTRICT - Nurlailis Saadah; Hilmi Yumni; Sri Mugianti; Budi Yulianto (Jurnal Berkala Epidemiologi, 2022)
Background: The condition of failure to thrive in toddlers due to chronic malnutrition and making children too short for their age is called stunting. Purpose: This research was conducted to analyze the risk factors of stunting in children.  Methods: The study was conducted from mid-May to mid-August 2020. This study developed a model for maternal empowerment in preventing and managing stunting using a cross-sectional design, then implementing the model using a quasi-experimental non-randomized pre-post control group design. The population involved was all mothers with children under five years old in Posyandu Ngariboyo, Candirejo, and Plaosan, obtaining 250 mothers. Meanwhile, the study sample was 150 mothers who had children under five years old in Posyandu Ngariboyo, Candirejo, who met the inclusion criteria. Results: Mothers with good characteristics increased their knowledge of stunting prevention and control by 0.42 times (p=0.01). Mothers with good knowledge increased their maternal commitment by 0.23 (p=0.01), and mothers who had good commitment reduced stunting by 0.45 (p=0.01). Furthermore, mothers with good knowledge increased the family support by 0.24 (p=0.01). In addition, good family support also reduced stunting by 0.26 (p=0.01). Conclusion: Mother's knowledge contributes to the prevention and management of stunting. Children's physical health, family support, nutritional status, and home environment are also important factors in stunting prevention and management. Family support is needed by mothers to realize their commitment to carrying out early detection, prevention, and control stunting.